Emotional responses to favorite and relaxing music predict music-induced hypoalgesia - Valevicius, Darius; Lépine Lopez, Anaïs; Diushekeeva, Ajar; Lee, April Chaewon; Roy, Mathieu (Frontiers in Pain Research, 2023)
The hypoalgesic effects of music on pain have long been established. However, the characteristics of music which are important for reducing pain have not been well-studied. Some research has compared subject-selected preferred music to unfamiliar music selected by researchers, and has typically found a superior effect from preferred music. In this study, we sought to discover what aspects of listeners’ relationship with their preferred music was important in producing a hypoalgesic effect. To do this, we conducted a thermal pain and music listening experiment with 63 participants (14 male, 49 female, mean age = 21.3) and conducted brief structured interviews about their favorite music. We first replicated the finding that favorite music outperforms experimenter-selected relaxing music in reducing pain unpleasantness (MD = -7.25, p < 0.001) and that the difference in hypoalgesia was partially mediated by an increase in musical chills (ab = -2.83, p < 0.01). We then conducted a theme analysis on the interview transcripts and produced four themes relating to emotional experience: moving/bittersweet, calming/relaxing, happy/cheerful, and energizing/activating. We found suggestive evidence that moving/bittersweet favorite music reduces pain unpleasantness through increased music pleasantness (ab = -5.48, p < 0.001) and more musical chills (ab = -0.57, p = 0.004), while the other three themes are associated with lower levels of musical chills. In summary, we find that music pleasantness and musical chills are salient predictors of music-induced hypoalgesia, and that different categories of favorite music derived from qualitative analysis may engage these emotional pathways to different degrees.